Leadership and work motivation on employee performance of panasea medika madiun clinic - Hidayat, Ichwan; Peristiowati, Yuly; Wardani, Ratna (CV. Paperhome Indonesia, 2025)
Background: The success of an organization is highly dependent on the quality of its human resources. Effective leadership is able to move and direct employees to work optimally, while high work motivation encourages employees to take the initiative and increase their creativity in achieving organizational goals. Employee work performance is the key to organizational success. The purpose of the study was to analyze the effect of leadership and employee work motivation on employee performance at Panasea Medika Clinic. Method : This study uses a quantitative design with a survey method. The research sample amounted to 114 respondents who were employees at the Panasea Medika Clinic inpatient installation. Data were collected using a questionnaire and analyzed using multiple linear regression analysis. Results: Bivariate analysis showed a significant influence between work motivation (p=0.000; r=0.533) and leadership (p=0.000; r=0.475) on work performance. Multiple linear regression analysis showed that the regression model can explain 40.2% of the variance in work performance. Work motivation is the most influential variable on work performance (p=0.000; B=0.315). Conclusion: both leadership and work motivation have a significant effect on employee performance at Panasea Medika Clinic Madiun. This study recommends that the management of Panasea Medika Madiun Clinic increase efforts to improve work motivation and leadership quality to improve employee performance. Future research can expand the research variables and consider other factors that may affect work performance.